Skills For Increasing Educational Efficiency Through Independent Study for Students of Higher Education Institutions - Ernazarova M.J. (Euro Asian Journal Publishing, 2024)
It is important to implement a special approach to the organization of independent educational activities of students, in which the personal approach is often carried out on the basis of selection through the content of the proposed tasks. In this article, the author reflects on the improvement of educational efficiency and the development of cognitive abilities of students of higher educational institutions today through independent education.
Keywords: independent education; independent activity; independent work